Advanced Dementia: The Black and White of Mechanical Ventilation for Pneumonia and Septicemia (SA518C) - Teno, Joan; Sharma, Rashmi; Curtis, J Randall; Khandelwal, Nita; Engelberg, Ruth; Mor, Vincent; Gozalo, Pedro; Meltzer, David (Journal of pain and symptom management, 2017)
An abstract of a study by Teno et al examining the use of mechanical ventilation in Black and White nursing home residents with advanced dementia who were hospitalized for pneumonia or septicemia is presented. Unlike feeding tube use, mechanical ventilation use among advanced dementia patients has substantially increased, with Blacks having a larger increase compared to Whites that is based, in part, on the hospitals where Blacks receive care.